Re-examining the relationship between measures of static and dynamic balance among young adults - Adriana Duquette; Micheline Senia; Paula van Wyk; Joseph Baker; Kate Paquin; Sean Horton (Bern Open Publishing, 2022)
Balance is essential to several activities of daily life, from the capacity to stand independently to the execution of complex sport movements. The extent to which balance can be improved has led researchers to consider whether underlying features of a general balance ability exists, and whether they can be used to predict performance on future balance tasks. Adjacent to this investigation is the debate between theorists who support a general motor ability (GMA) and those who advocate for motor specificity. The notion of task specificity has been supported within the literature, such as the highly cited study by Drowatzky and Zuccato (1967) that compared balance tasks, finding weak correlations between tasks assessed. The purpose of the current study was to replicate this classic study using a more mature, contemporary sample and investigate the relationship between six static and dynamic measures of balance among a young adult population to determine if there is continuing support for this notion. Standardized instructions and procedures were followed when completing the Stork Stand Test, Diver's Stand Test, Bass Lengthwise Stick Test, Sideward Leap Test, Modified Bass Stepping Stone Test, and a Modified Balance Beam Test. Five hundred and seventy university students completed these six balance performance tests. A Spearman's rank-order correlation test, assessing the relationship between the results, revealed significant weak to moderate correlations. These results contrasted with the original study that yielded weak correlations between balance tasks, with only one correlation reaching significance (Drowatzky & Zuccato, 1967). While the nature of the tasks assessed made it difficult to draw conclusions with respect to the motor specificity hypothesis, they allowed further reflection on the complexity of balance, and on the specificity of practice hypothesis, thus calling to revisit the debate.